2021
DOI: 10.3390/v13091792
|View full text |Cite
|
Sign up to set email alerts
|

A Waterborne Gastroenteritis Outbreak Caused by a GII Norovirus in a Holiday Camp in Catalonia (Spain), 2017

Abstract: On 2 February 2017, Epidemiological Surveillance Services were notified of an outbreak of acute gastroenteritis (AGE) among schoolchildren who had taken part of a school trip from 30 January to 3 February 2017 at a holiday camp in Catalonia. A retrospective cohort study was performed to identify the causative agent, estimate the magnitude of the outbreak and identify its source, as well as to determine the route of transmission. Data collected by standardised questionnaires identified 41 episodes of AGE among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
1
7
1
Order By: Relevance
“…In our study, 52.63% of outbreaks occurred in the fall and winter months (October to March), similar to the 68% found by Steele et al in outbreaks in the US in 2009 ( 21 ). Ahmed et al in a meta-analysis of 293 studies found that 71% of outbreaks occurred in the cold months of the year (October to March in the Northern hemisphere and April to September in the Southern hemisphere) ( 14 ).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In our study, 52.63% of outbreaks occurred in the fall and winter months (October to March), similar to the 68% found by Steele et al in outbreaks in the US in 2009 ( 21 ). Ahmed et al in a meta-analysis of 293 studies found that 71% of outbreaks occurred in the cold months of the year (October to March in the Northern hemisphere and April to September in the Southern hemisphere) ( 14 ).…”
Section: Discussionsupporting
confidence: 64%
“…In our study only one outbreak was waterborne with an attack rate of 64.1% ( 21 ), clearly larger that the attack rate in all common source transmission outbreaks (33.42%) or in all studied outbreaks (25.7%). Waterborne outbreaks reported by other authors also show a large number of affected people ( 22 , 23 ).…”
Section: Discussioncontrasting
confidence: 46%
“…Recently, Carol et al (2021) investigated the causative agent responsible for an outbreak of acute gastroenteritis (AGE) among 174 pupils that were involved in a school trip between 30 January and 3 February 2017 at a holiday camp in Catalonia. The authors discovered about 41 episodes of AGE with symptoms ranging from abdominal pain (73.8%), nausea (64.3%), vomiting (54.8%), diarrhea (45.2%), and headache (42.9%).…”
Section: Public Health Implications Of Waterborne Enteric Viral Diseasesmentioning
confidence: 99%
“…Consequently, noroviruses are not directly detected in water samples in most suspected norovirus waterborne outbreaks. In Spain, waterborne outbreaks associated with norovirus infection have been rarely reported in the literature, with only 6 outbreak investigations published since 1995 ( 8 13 ). These outbreaks were associated with sources of infection such as bottled mineral water, spring water, or municipal drinking water systems, but norovirus was directly detected in water samples in only half of these outbreaks.…”
Section: Introductionmentioning
confidence: 99%